Cover Picture: Monolithic, Crystalline MOF Coating: An Excellent Patterning and Photoresist Material (ChemNanoMat 5/2015). Issue 5 (31st August 2015) - Wang, Zhengbang; Liu, Jinxuan; Grosjean, Sylvain; Wagner, Danny; Guo, Wei; Gu, Zhigang; Heinke, Lars; Gliemann, Hartmut; Bräse, Stefan; Wöll, Christof
Abstract : The Front Cover illustrates the photopatterning of metal–organic framework (MOF) thin films. Azido‐ and alkyne‐based SURMOFs (surface‐anchored MOFs) were prepared using a liquid‐phase epitaxial (LPE) process using an automated spray system. Lateral structuring of these monolithic, highly homogeneous coatings was achieved by photo‐controlled post‐synthetic modification (PSM) of the ligands comprising the molecular framework. More details can be found in the Full Paper by C. Wöll, et al. onpage 338 in Issue 5, 2015 . (DOI:10.1002/cnma.201500031 ).